Free‐Standing SnO2/Nitrogen‐Doped Graphene Films as High‐Performance Binder‐Free Electrodes for Flexible Lithium‐Ion Batteries. Issue 12 (4th November 2015) - Fan, Hua; Liang, Junfei; Zheng, Jinlong; Qi, Juanjuan; Yang, Jie; Hu, Pengfei; Zhao, Hewei; Liu, Juzhe; Guo, Lin
Abstract: It is currently urgent to develop flexible lithium‐ion batteries (LIBs) because of the growing interest and strong market demand of flexible or bendable electronics. However, the large‐scale use of flexible LIBs is mainly limited by our capability to fabricate high‐performance flexible electrodes. Here, we develop a facile, cost‐efficient, and eco‐friendly strategy to prepare flexible SnO2 /nitrogen‐doped graphene films (SNGFs) for LIBs. Significantly, the obtained binder‐free, conducting agent‐free, and current collector‐free flexible electrodes exhibited high capacity, excellent cycling stability, and superior rate capability. The outstanding Li storage performance of the SNGF is primarily ascribed to its specific structure, and indicates its great potential as an anode material for flexible LIBs. Our new approach for the fabrication of flexible electrodes can be applied to various other electrode materials, which may be useful in flexible or bendable energy storage devices. Abstract : Standing tall: Flexible lithium‐ion batteries (LIBs) are of interest because of the growing market demand of flexible or bendable electronics. Here, the authors develop a facile, cost‐efficient, and eco‐friendly strategy to prepare flexible SnO2 /nitrogen‐doped graphene films (SNGFs) for LIBs. Significantly, the obtained binder‐free, conducting agent‐free, and current collector‐free flexible electrodes exhibit high capacity, excellent cycling stability, and superior rate capability.